The presence of anaemia negatively influences survival in patients with POLG disease. Issue 6 (1st September 2017) - Hikmat, Omar; Charalampos, Tzoulis; Klingenberg, Claus; Rasmussen, Magnhild; Tallaksen, Chantal M. E.; Brodtkorb, Eylert; Fiskerstrand, Torunn; McFarland, Robert; Rahman, Shamima; Bindoff, Laurence A.
Abstract: Background: Mitochondria play an important role in iron metabolism and haematopoietic cell homeostasis. Recent studies in mice showed that a mutation in the catalytic subunit of polymerase gamma ( POLG ) was associated with haematopoietic dysfunction including anaemia. The aim of this study was to analyse the frequency of anaemia in a large cohort of patients with POLG related disease. Methods: We conducted a multi‐national, retrospective study of 61 patients with confirmed, pathogenic biallelic POLG mutations from six centres, four in Norway and two in the United Kingdom. Clinical, laboratory and genetic data were collected using a structured questionnaire. Anaemia was defined as an abnormally low haemoglobin value adjusted for age and sex. Univariate survival analysis was performed using log‐rank test to compare differences in survival time between categories. Results: Anaemia occurred in 67% (41/61) of patients and in 23% (14/61) it was already present at clinical presentation. The frequency of anaemia in patients with early onset disease including Alpers syndrome and myocerebrohepatopathy spectrum (MCHS) was high (72%) and 35% (8/23) of these had anaemia at presentation. Survival analysis showed that the presence of anaemia was associated with a significantly worse survival ( P = 0.004). Conclusion: Our study reveals that anaemia can be a feature of POLG ‐related disease. Further, we show that its presence is associated with significantly worse prognosis either because anaemia itself is impacting survival or because it reflects the presence of more serious disease. In either case, our data suggests anaemia is a marker for negative prognosis.